2021
DOI: 10.21037/jtd-21-1032
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of digital tomosynthesis to evaluate silicone airway stents and related complications

Abstract: Background: Digital tomosynthesis (DTS) is an imaging technique with benefits in reconstructing sequential cross-sectional images. We evaluated the diagnostic performance of DTS for silicone airway stents and stent-related complications in patients who underwent bronchoscopic intervention. Methods: This retrospective study included patients who underwent bronchoscopic intervention after chest radiography (CXR) and DTS examinations from September 2013 to August 2020. The interval between CXR, DTS, and bronchosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Due to the antiproliferative properties shown, the PDMS/ZnO-T composite materials might be also useful for other medical indications, e.g., tracheobronchial airway stents, as postoperative fibrosis is also a known complication [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the antiproliferative properties shown, the PDMS/ZnO-T composite materials might be also useful for other medical indications, e.g., tracheobronchial airway stents, as postoperative fibrosis is also a known complication [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…However, based on our experience, we recommend digital tomosynthesis and spirometry for routine surveillance after the procedure. In our previous study, digital tomosynthesis demonstrated greater sensitivity and accuracy than simple chest radiography to identify silicone airway stents and silicone stent-related complications [34]. Moreover, the patient is exposed to a lower radiation dose than in CT.…”
Section: Which Is the Most Appropriate Technique?mentioning
confidence: 97%